2009
DOI: 10.1557/proc-1218-z07-02
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Soldier-Based Thermoelectric Power Systems Using Battlefield Heat Sources

Abstract: The U.S. military uses large amounts of fuel during deployments and battlefield operations. Consequently, the U.S. military has a strong need to develop technologies that increase fuel efficiency and minimize fuel requirements all along the logistics trail and in all battlefield operations. There are additional requirements to reduce and minimize the environmental footprint of various military equipment and operations and reduce the need for batteries (nonrechargeable) in battlefield operations. The tri-agency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In particular, for the only fracture data that are 20 and Ag 0.9 Pb 9 Sn 9 Sb 0.6 Te 20 specimens included in this study. Finite-element analysis performed by Pacific Northwest National Laboratory (PNNL) 42 indicates that, with the appropriate dimensions and interconnections, the thermal stresses generated within the thermoelectric modules fabricated from Ag 0.86 Pb 19+x SbTe 20 and Ag 0.9 Pb 9 Sn 9 Sb 0.6 Te 20 elements may not exceed the strength values measured in this study. Also, while thermal fatigue testing was done only on nonsegmented specimens of LAST or LASTT, numerical simulations of segmented legs would also be of interest.…”
Section: Segmented-leg Modulesmentioning
confidence: 69%
“…In particular, for the only fracture data that are 20 and Ag 0.9 Pb 9 Sn 9 Sb 0.6 Te 20 specimens included in this study. Finite-element analysis performed by Pacific Northwest National Laboratory (PNNL) 42 indicates that, with the appropriate dimensions and interconnections, the thermal stresses generated within the thermoelectric modules fabricated from Ag 0.86 Pb 19+x SbTe 20 and Ag 0.9 Pb 9 Sn 9 Sb 0.6 Te 20 elements may not exceed the strength values measured in this study. Also, while thermal fatigue testing was done only on nonsegmented specimens of LAST or LASTT, numerical simulations of segmented legs would also be of interest.…”
Section: Segmented-leg Modulesmentioning
confidence: 69%
“…However, thermal annealing of the tumbled capacitors can restore mechanical strength [134]. While it has been suggested that chamfering to the edges of TE legs could both relieve the stress concentration due to sharp corners and (ideally) remove microcracks induced by cutting operations [135], the chamfering process itself may introduce crack damage. Thermal annealing the specimens in an inert atmosphere at T h ≈ 0.6 could diffusively heal and strengthen the legs.…”
Section: Microcrackingmentioning
confidence: 99%
“…Thermoelectric (TE) energy recovery and conversion systems is an important technology for recovering this waste thermal energy and converting it to useful electrical energy, either by itself or as a critical energy conversion subsystem in a hybrid power system. Yazawa and Shakouri [16] attempted to address this question with a simplified, closed-form analysis of the quite complex thermal and thermoelectric design interactions described in earlier references [3][4][5][6][7][8][9][10][11][12][13][14][15]. Thermoelectric (TE) power systems in these applications require high performance hot-side and cold-side heat exchangers to provide the critical temperature differential and transfer the required thermal energy to create the power output.…”
Section: Introductionmentioning
confidence: 99%